Open Distance Learning (ODL) experience among students in Malaysia / Muhammad Nabil Izani …[et al.] - Izani, Muhammad Nabil; Mohd Zaid, Muhammad Adam Syafiq; Muhmmad Zin, Fatin Akma; Md Azmi, Nur Ayuni; Abdullah, Wan Edzzuddin Najmi (Universiti Teknologi MARA (UiTM), 2020)
Open Distance Learning (ODL) is a one of method of learning that triggers off the problem especially to students. Moreover, nowadays, the whole world faces the covid-19 pandemic that contributes to increasingly people’s death. This causes many societies to lose their jobs and become very hard for them to work as usual. With this chaos situation, the student forcibly uses technology such as smartphone or computer to undergo the situation learning in open distance learning. Now, after a few months of ODL conducting, a lot of innovations of teaching and learning are happening. The tutors have done their best and work hard to help students through the challenging teaching and learning. According to Vice Chancellor of Universiti Teknologi Mara (UiTM), Prof. Emeritus Datuk Ir. Dr. Mohd Azraai Kassim, mentions that business affairs, teaching and learning, administrative affairs and etc are new habits online and it is becoming a necessity for today’s lifestyle. Most students are more comfortable using methods on face to face learning than the ODL. Open distance learning is one of the most rapidly growing fields of education nowadays and it has a substantial impact on all education delivery systems. The new ODL system is growing fast because of the development of internet-based information technologies and in particular the World Wide Web. The concept of ODL education happens where the tutor and students stay in separate locations and become for them to communicate with each other long distance. In addition, open distance learning also occurs between two people which is between tutor such as teachers and lecturers and students that are difficult to communicate with. However, ODL also may both of them cannot come close to each other to make the entire education system flexible.